Portfolio optimization using forward-looking information - Alexander Kempf; Olaf Korn; Sven Saßning (University of Cologne, Centre for Financial Research (CFR), 2014)
We develop a new family of estimators of the covariance matrix that relies solely on forwardlooking information. It uses only current prices of plain-vanilla options. In an out-of-sample study we show that a minimum-variance strategy based on these fully-implied estimators outperforms several benchmark strategies, including various strategies based on historical estimates, index investing, and 1/N investing. The outperformance originates in crisis periods when information ow and information asymmetry are high. Although the historical benchmark strategies improve when more recent data is used, they never outperform fully-implied strategies. Thus, our results suggest that investors are better off relying on forward-looking information.
Keywords: G11; G13; G17; 330; portfolio selection; option-implied information